Effect of Benfotiamine in Podocyte Damage Induced by Peritoneal Dialysis Fluid - Müller-Krebs, Sandra; Nissle, Katharina; Tsobaneli, Julia; Zeier, Martin; Kihm, Lars Philipp; Kender, Zoltan; Fleming, Thomas; Nawroth, Peter Paul; Reiser, Jochen; Schwenger, Vedat (Frontiers in Medicine, 2015)
Background: In peritoneal dialysis (PD) residual renal function (RRF) fundamentally contributes to improved quality of life and patient survival. High glucose and advanced glycation end-products (AGE) contribute locally to peritoneal and systemically to renal damage. Integrity of podocyte structure and function is of special importance to preserve RRF. Benfotiamine could counteract the glucose and AGE mediated toxicity by blocking hyperglycemia associated podocyte damage via the pentose phosphate pathway. Methods: A human differentiated podocyte cell line was incubated with control solution (Control), 2.5% glucose solution (Glucose) and 2.5% PD fluid (PDF) for 48 h either ± 50 μM benfotiamine. Podocyte damage and potential benefit of benfotiamine were analyzed using immunofluorescence, western blot analysis, and a functional migration assay. For quantitation, a semiquantitative score was used. Results: When incubating podocytes with benfotiamine, Glucose and PDF mediated damage was reduced resulting in lower expression of AGE and intact podocin and ZO-1 localization. The reorganization of the actin cytoskeleton was restored in the presence of benfotiamine as functional podocyte motility reached Control level. Decreased level of inflammation could be shown as well as reduced podocyte apoptosis. Conclusions: These data suggest that benfotiamine protects podocytes from Glucose and PDF mediated dysfunction and damage, in particular with regard to cytoskeletal reorganization, motility, inflammation and podocyte survival.